Mapeamento da vulnerabilidade do aquífero à contaminação no município de Boa Vista do Cadeado/RS - Nascimento, Leandro Meirelles do (2013)
The pollution generated by human activities has aroused the continuing need to map and assess the conditions of the environment in relation to possible sources of contamination, especially harmful to groundwater resources. The study, for the city of Boa Vista do Cadeado in the Rio Grande do Sul State, located in northwest riograndense, is inserted in the Province of the Southern Plateau Brazilian Geomorphological where spills outcrop of volcanic rocks forming the Serra Geral Aquifer System / SGAS. Spatialize in thematic maps hydrodynamic data of wells related to: the static water level, flow rate, the potentiometric surface, the specific capacity and vulnerability indices natural fissure aquifer contamination. Using the system GOD, were simulated by funding 12 wells, which contained all the information necessary for their application. We obtained two classes of natural vulnerability, and 83.3% in class insignificant and 16.7% in low class. It was concluded that the region presents little vulnerable to contamination having a natural protection due to volcanic basalt rock layers in confined aquifer and a mean water level, slightly deeper. The catchment wells are at odds with the standards constructive, as well as with the environmental legislation of the State, therefore, must be appropriate in order to protect the fountain groundwater.